PENGARUH KOMPETENSI APARATUR DAN KECURANGAN TERHADAP TATA KELOLA KEUANGAN PEMERINTAH PROVINSI MALUKU UTARA DENGAN INTERVENING PENGENDALIAN INTERN - Yunus, Imran (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
The purpose of this study is the influence of apparatusl competence, fraud , entern control on financial gofernance and apparaturs competency,cheating on on intern control SKPD of the north Maluku Provincial government, the type of research is explanation. Respondents in this study were financial administrators, technical executives of activities, and treasurers of 43 SKPD expenditure in the North Maluku Provincial government. The data collected is processed with statical methods used to test the hypothesis directly and indirectly the results of the study show that, first the competency of the fraud apparatus, and internal controls affecte financial governance, both apparatus copeten ciesinfluence internal control, the tree internal controls affect financial governance.